Is the Paradigm of Tabellionis Officium Fideliter Exercebo Aligned with the Cyber Notary Concept in Indonesia’s Public Notary Development? - Resen, Made Gde Subha Karma; Dewi , Ni Putu Kompiang Ratna (Universitas Negeri Semarang, 2025)
The concept of the cyber notary emerged to address the need for legal recognition and to resolve issues regarding electronic transactions. The rise of electronic transactions defined by remote exchanges, along with the advancements of the 4.0 Industrial Revolution—characterized by automation and digitalization—has driven the development of various technological adaptations in notarial practices in Indonesia. However, notaries, in performing their duties and authority, are bound by the principle of Tabellionis Officium Fideliter Exercebo. This principle requires notaries to work traditionally. The problems discussed in this research are: (1) What is the concept of cyber notary from a comparative perspective? and (2) Is the Paradigm of the Principles of Tabellionis Officium Fideliter Exercebo in line with the concept of cyber notary? This scholarly article employs normative legal research, utilizing a statutory approach, a conceptual approach, and a comparative approach. Neither France nor the United States uses the term of 'cyber notary' or 'electronic notary' as these concepts were initially conceived to address issues related to electronic transactions. In Indonesia, the term 'cyber notary' has been adopted to study various technological adaptations in notarial work, resulting in misunderstanding of the terminology and its intended meaning. This has confused cyber notary research. The concept of the cyber notary is not directly aligned with the principle of Tabellionis Officium Fideliter Exercebo. Instead, technological adaptations in notarial work should be explored under the framework of Modernization of Notarial Practice,' while maintaining adherence to the Tabellionis Officium Fideliter Exercebo principle.